Synthesis and Characterisation of Sulphur-Functionalised Silica Nanocapsules for Mercury Removal Process - Palaniappan, Thenappan (Universiti Teknologi PETRONAS, 2016)
Sulphur functionalized silica nanocapsules (S-SiNC) was successfully synthesised and characterized as a potential mercury adsorbent. The synthesis of S-SiNC was carried out using the soft-templating method using cetyl trimethylammonium bromide (CTAB) as cationic surfactant, toluene as co-solvent, ammonia solution as catalyst, elemental sulphur as precursor and tetraethyl orthosilicate (TEOS) as the silica base. The S-SiNC adsorbent was characterized using scanning electron microscope (SEM), transmission electron microscope (TEM), Fourier transformed infrared spectroscopy (FTIR) and nitrogen adsorption/desorption analysis. The mercury (Hg) adsorption was carried out in a batch adsorption process with variation in initial Hg (II) concentration. The results show that blank SiNC and S-SiNC has a BET surface area in the range of 150-200 m2 /g and all of the adsorbents displays good efficiency in mercury ion adsorption (qe=107.87 mg/g). The experimental data obtained was found to be fitting well to the Langmuir isotherm model (R2= 0.979) compared to Freundlich isotherm model. Thus, the presence of sulphur functional groups, especially elemental sulphur (ES) in the SiNC, gave a significant enhancement of Hg (II) adsorption capacity.